1999
DOI: 10.1097/00000542-199909000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Inhibitory Effect of Propofol on the Contraction of Canine Airway Smooth Muscle 

Abstract: Propofol attenuates the muscarinic receptor-mediated airway muscle contraction. The mechanism underlying these effects was attenuation of inositol phosphate generation and inhibition of Ca2+ mobilization through the inhibition of the receptor-coupled signal-transduction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…This latter set of experiments adds yet another possible explanation for propofol’s preferential protection from reflex-induced bronchoconstriction during intubation which has traditionally been attributed to its action on airway efferent parasympathetic cholinergic nerves and less convincingly to post-junctional modulation of L-type calcium channels 32 or inositol phosphate signaling 33 in airway smooth muscle itself. However, these previous studies have illustrated these smooth muscle effects only at concentrations of propofol (>100uM) above those typically achieved clinically 3436.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This latter set of experiments adds yet another possible explanation for propofol’s preferential protection from reflex-induced bronchoconstriction during intubation which has traditionally been attributed to its action on airway efferent parasympathetic cholinergic nerves and less convincingly to post-junctional modulation of L-type calcium channels 32 or inositol phosphate signaling 33 in airway smooth muscle itself. However, these previous studies have illustrated these smooth muscle effects only at concentrations of propofol (>100uM) above those typically achieved clinically 3436.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies in airway tissues from humans and animal models have shown that propofol can attenuate contractile responses from acetylcholine 3739, histamine 40 and endothelin 39, but only at concentrations of 100–300uM. These previous studies which only demonstrated a propofol effect at high concentrations have largely focused on cellular signaling pathways involved in the initiation and maintenance of contraction (L-type calcium channels 32, intracellular calcium changes 40,41 or inositol phosphate synthesis 33). Conversely, in the present study, lower concentrations of propofol (20uM) facilitated airway smooth muscle relaxation likely due to different signaling pathways regulating relaxation28 as opposed to those regulating contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is lipid-soluble, and it attenuates the airway smoothmuscle contraction induced by ACh [13], shifting the dose-response curve of carbachol (CCh)-induced airway smooth-muscle contraction to the right. Lin et al [14] reported that propofol also decreased the release of Ca 2+ from internal stores and decreased Ca 2+ influx, and that it attenuated CCh-induced inositol phosphate accumulation in canine airway smooth muscle. Thus, it is likely that propofol could inhibit the activation by ATP of the PI response through G-protein-coupled PLC, resulting in the relaxation of ATP-induced contraction of the airway smooth muscle.…”
Section: Resultsmentioning
confidence: 99%
“…The dose required for tracheal smooth-muscle relaxation in the present study was out of the clinical range. Lin et al [14] reported that, although propofol at 10 mM significantly attenuated the increased intracellular Ca 2+ concentration induced by CCh in cultured canine tracheal smooth muscle cells, it was necessary to have a dose of at least 100 mM of propofol to shift the dose-contraction curves of CCh in isolated trachea to the right. They concluded that the need for this higher dose may have been caused by the more complete distribution of propofol in cultured cells than in intact tissues, and that higher doses of propofol may be needed to cross the connective tissues to reach smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Propof ol attenuates tracheal smooth muscle contraction induced by carbachol (1), histamine (2,3), and other mediators (4,5). The mechanisms involved in this effect include a propofol-induced decrease in the release of Ca 2ϩ from internal stores and also inhibition of Ca 2ϩ influx (1). In addition, propofol attenuates inositol phosphate accumulation (1) and inhibits voltage-dependent Ca 2ϩ channels of tracheal smooth muscle cells (6).…”
mentioning
confidence: 99%